RESEARCH OF THE TEMPERATURE FIELD PROFILES OF THE DRYING PROCESS OF PLANT RAW MATERIALS USING A SOLAR-WATER HEATING DRYING EQUIPMENT - Sultanova, A.; Safarov, J. E.; Jumayev, B. M.; Dadayev, G. T. (International Journal of Psychosocial Rehabilitation, 2020)
This research of the profiles of the temperature field of the process of convective drying of plant raw materials. Mathematical modeling of the temperature field on the basis of the three-phase flow structure was carried out. In a wide range of variation of design and operating parameters (from 50 to 150%) their nominal values are identified. A qualitatively new picture of the temperature field was found, which is expressed in the fact that, depending on the contact conditions of the gas and solid phases and the relative air flow, the temperature profile on the pallets can have both positive and negative slopes. The sensitivity of this relationship, formalized in the form of axonometric graphs and the corresponding families of isolines on the plane of variable factors, is shown. Criteria for non-uniformity of temperature profiles across pallets (dispersion of material temperature and angle of inclination of the approximating straight line with fixed values of the average temperature of the substance) are proposed. The procedure for solving the optimization problem on the conditions of the minimum criterion for the unevenness of the material profile is justified when the average temperature of the material specified in accordance with the conditions of the process schedule is restricted as equality